Pakistan : An Assessment of the Medium-Term Development Framework - World Bank (Washington, DC, 2014)
The Policy Note is an assessment of the Medium-Term Development Framework (MTDF), along with an estimate of the projected budgetary impact of the Framework, and an elaboration of some specific critical aspects. The MTDF is the Pakistani version of a higher education strategy. It is assessed for soundness, consistency, and realism of the objectives and associated programs. The Note tests the MTDF through the simulation of budgetary impact, and proposes alternative scenarios for funding the development of universities and the higher education subsector from both public and private sources. The Note complements the MTDF in the following areas: quality, relevance, and accreditation; public and private partnerships; governance and management; costs and financing of the MTDF; and communication.